The Effect of Capital Structure, Financial Performance, Firm Growth and Size on Firm Value: Empirical Study on Manufacturing Listed Companies on the Indonesia Stock Exchange - Hutauruk, Rapat Piter Sony; Zalukhu, Rika Surianto; Collyn, Daniel (International Journal of Business, Economics & Financial Studies, 2023)
Today, companies in the industry and the current economic conditions have created tight competition between manufacturing companies. Competition in the manufacturing industry makes every company improve its performance so that its goals can still be achieved. A high company value is the desire of every company owner because a high company value indicates the prosperity of its shareholders is also high. This study analyses the effect of capital structure, financial performance, firm growth, and size on firm value. This type of research was descriptive quantitative. The study was conducted on 181 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019. The research sample was 41 companies. The sampling technique used was purposive. The type of data used is secondary data. Data were analyzed using multiple linear regression analysis methods. The results show that financial performance partially has a positive and significant effect on firm value. Meanwhile, capital structure, firm growth, and firm size partially have a positive and insignificant effect on firm value.